The Development of Reading Skills for Grade 1 Students Using the Phonics Teaching Method - Intaranaronk, Usa; Nakin, Sirirat (Ratchaphruek Journal, 2022)
The purposes of this research were to compare 1) the reading skills of first-grade students before and after learning by using the phonics teaching method, and 2) the reading skills of first-grade students after learning with 70% criterion. The samples in this study were 14 first-grade students of Bankhokkrachainoonkum school obtained by cluster random sampling in the second semester of the academic year 2021. The instruments employed in this study consisted of 5 lesson plans. The data was collected by using a reading skill test. The Data was analyzed by using percentage, Mean, Standard deviation, and t-test. The results of the reading skill of first-grade students study indicated the following: 1) after learning by using the phonics teaching method before learning, it was significantly higher at the .05 level, and 2) after learning by using the phonics teaching method at significantly higher than 70% criterion, it revealed the .05 level statistical significance.